Prevention of Iron Deficiency Anemia Through Blood Immunochemical Detection in Improving the Quality of Life of Elderly - Christina Destri Wiwis Wijayanti; Dheasy Herawati; Andita Ayu Mandasari; Herin Mawarti (Eduvest - Journal of Universal Studies, 2025)
The increase in the elderly population poses challenges to health services in Indonesia, particularly regarding degenerative diseases and malnutrition due to reduced physical activity and dietary changes. Supporting the Asta Cita program for elderly assistance, it is essential to monitor elderly health to maintain wellness and functionality in old age. This study used descriptive analytical observation on 25 women aged 55 to 75 years. Results showed that hemoglobin levels declined below the normal range of 12–15 g/dL. Serum iron levels and lactate dehydrogenase (LDH) enzyme activity were measured using a spectrophotometer to assess anemia potential, while immune status was evaluated through vitamin D levels by immunofluorescence. Statistical analysis with SPSS software using Spearman’s correlation test revealed no significant relationships between hemoglobin and serum iron (p = 0.520), hemoglobin and LDH (p = 0.615), or serum iron with LDH (p = 0.543) and vitamin D (p = 0.138). Pearson correlation showed no association between hemoglobin and vitamin D (p = 0.885). These findings indicate weak or no correlation among these parameters in this sample. Factors such as small sample size and measurement limitations suggest that using more precise biomarkers, like Ferritin levels, could improve future research. This study contributes to understanding Prevention of Iron Deficiency Anemia Through Blood Immunochemical Detection in Improving the Quality of Life of Elderly—a valuable approach to elderly health monitoring.